Engineering of Biocompatible Coacervate-Based Synthetic Cells - van Stevendaal, Marleen H. M. E. (ACS Appl Mater Interfaces, 2021)
[Image: see text] Polymer-stabilized complex coacervate microdroplets have emerged as a robust platform for synthetic cell research. Their unique core–shell properties enable the sequestration of high concentrations of biologically relevant macromolecules and their subsequent release through the semipermeable membrane. These unique properties render the synthetic cell platform highly suitable for a range of biomedical applications, as long as its biocompatibility upon interaction with biological cells is ensured. The purpose of this study is to investigate how the structure and formulation of these coacervate-based synthetic cells impact the viability of several different cell lines. Through careful examination of the individual synthetic cell components, it became evident that the presence of free polycation and membrane-forming polymer had to be prevented to ensure cell viability. After closely examining the structure–toxicity relationship, a set of conditions could be found whereby no detrimental effects were observed, when the artificial cells were cocultured with RAW264.7 cells. This opens up a range of possibilities to use this modular system for biomedical applications and creates design rules for the next generation of coacervate-based, biomedically relevant particles.